Research and optimization of a multilevel fire detection framework based on deep learning and classical pattern recognition techniques - Qi Liu; Hong Chen; Da Lin (Scientific Reports)
Abstract Fire detection technology is essential for safeguarding public safety and minimizing property damage. Despite advancements in both traditional methodologies and modern deep learning models, challenges such as suboptimal accuracy and elevated false alarm rates persist, particularly in complex environmental scenarios. This paper introduces the Fire Focused Detection Network (FFDNet), a state-of-the-art flame detection framework that seamlessly integrates classical approaches with deep learning strategies. By leveraging an enhanced Real-Time DEtection TRansformer (RT-DETR) model alongside the Vector Quantized Generative Adversarial Network (VQGAN), our methodology not only enhances flame detection sensitivity and precision but also significantly reduces false alarm frequencies. Specifically, we have integrated a novel loss function, the Innovative Minimum Perimeter Distance IoU (InnMPD-IoU), into the RT-DETR model, enabling the identification of a wider range of flames and flame-like phenomena. Additionally, the use of Complete Local Binary Pattern (CLBP) technology for texture feature extraction, combined with VQGAN technology for accurate flame identification through sample reconstruction, underscores our innovative approach. The experimental results demonstrate the exceptional performance of the model, achieving precision, recall, F1 score, and accuracy rates of 98.23%, 96.33%, 97.33%, and 95.08%, respectively, on the Dataset for Fire and Smoke Detection (DFS), substantially surpassing existing methods. Our objective is to further develop FFDNet into a robust, efficient, and widely applicable tool for flame detection, thereby providing significant technical support for fire prevention and response initiatives.